Activating the Contribution of the Court of Accounts in the Promotion of Good Governance in Accordance with the Vision of INTOSAI According to the Constitutional Amendment of 2020 - Moussaoui, Abdelaziz; Meddahi, Otman (Journal of Legal Studies and Researches, 2022)
This research deals with the legislative requirements available to the court of accounts in Algeria to reach the goal in promoting a good governance, and the legislative requirements to ensure its independence in order to accomplish this role. The research has concluded that the court of accounts has a relative independence. The organic law will organize the court’s assignments after the constitutional amendment of 2020.